2021
DOI: 10.1021/acsagscitech.1c00093
|View full text |Cite
|
Sign up to set email alerts
|

Greener One-Pot Synthesis of Gold Nanoparticle Glycoconjugates Using Functionalized Sugars

Abstract: Carbohydrates have been used to decorate metallic nanoparticles to form nanoglycoconjugates. However, the synthetic conditions typically require the utilization of increased temperatures and other reagents that negatively impact the stability of the conjugates. For the first time, this study is reporting the synthesis of gold–nanoparticle glycoconjugates (AuNP-GCs) in aqueous media at ambient temperatures. A series of sugars and small molecules acting as reducing, capping, and stabilizing agents were reacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…S2 A shows the absorbance at 370 nm due to a metallic iron oxide core that confirms the presence of LpAB-FeNP [ 46 ]. The decrease in the absorbance intensity after the conjugation process indicates the successful attachment of anti-VEGF to LpAB-FeNP [ 47 , 48 ]. In this study, the morphology of LpAB-FeNP and LpAB-FeNP/anti-VEGF was observed by scanning electron microscopy (SEM), as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2 A shows the absorbance at 370 nm due to a metallic iron oxide core that confirms the presence of LpAB-FeNP [ 46 ]. The decrease in the absorbance intensity after the conjugation process indicates the successful attachment of anti-VEGF to LpAB-FeNP [ 47 , 48 ]. In this study, the morphology of LpAB-FeNP and LpAB-FeNP/anti-VEGF was observed by scanning electron microscopy (SEM), as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…20 The hydroxyl groups in sugar molecules are reported to enhance the stability of nanoparticles, and oxidation of sugar is not required for the reduction of metals. 39 Supramolecular gel network of amphiphilic glycolipid gelator portrayed a crucial role in stabilizing the GNP. Balanced designing of gelator molecule is an essential factor for efficient reduction and stabilization of GNP within the gel.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of gold nanoparticle glycoconjugates based on functionalised sugars was recently reported [ 214 ]. The gold nanoparticle glycoconjugates were subsequently employed in the development of a sensor for the detection of the spores and hyphae of the blue-green mould Penicillium italicum in fruit [ 215 ].…”
Section: Nanosensor Applications In Plantsmentioning
confidence: 99%